2020
DOI: 10.1088/1757-899x/993/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Quality of Service in VANET

Abstract: VANET as Inter-vehicle communication is becoming a promising area of research, standardization, and growth with the ever-growing number of vehicles equipped with computer technology and wireless communication tools. Due to its erratic portability and the interrupted availability of a network, VANET is relatively incomprehensible for a strong end to end communication, In Vehicular Network the main advantage is that it communicates by using nodes. Because of its simple and basic method of communication, MANET is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…An application of such models for solving specific issues related to QoS can be observed from Reference 30, wherein deadline, data size, and time of arrival is considered for providing high QoS and improving the scalability of the VANET deployment. Similar models and solutions can be observed from References 2,23,31, wherein different algorithms to solve issues like heterogeneity, QoS‐awareness, security, stateless routing, and trust modeling are described. These methods allow SDN architectures to have better security, and QoS/E performance under a wide variety of network conditions.…”
Section: Literature Reviewmentioning
confidence: 74%
See 1 more Smart Citation
“…An application of such models for solving specific issues related to QoS can be observed from Reference 30, wherein deadline, data size, and time of arrival is considered for providing high QoS and improving the scalability of the VANET deployment. Similar models and solutions can be observed from References 2,23,31, wherein different algorithms to solve issues like heterogeneity, QoS‐awareness, security, stateless routing, and trust modeling are described. These methods allow SDN architectures to have better security, and QoS/E performance under a wide variety of network conditions.…”
Section: Literature Reviewmentioning
confidence: 74%
“…A study of different QoS parameters can be observed from Reference 22, wherein various routing protocols are compared for evaluation of E2E delay, PDR, jitter, energy consumption, and routing overheads in the network. Application of SDN in VANETs allows for improvement of these parameters as observed from References 23‐26; wherein different aspects of VANET including security, QoS, routing path estimation, trust improvement, and QoE improvement using edge computing are described. Blockchains can also be added to VANETs as discussed previously and confirmed using Reference 27 to improve their security performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using Zigbee, a wearable ECG was developed to communicate with master tracking devices [90]. In biomedical applications, improved Zigbee was considered [91] using a low-power transmitter and receiver to increase reliability in terms of interference. Overall, Zigbee performs reasonably and is suitable for healthcare applications owing to its high level of security and robustness to interference.…”
Section: Zigbeementioning
confidence: 99%
“…The current era of application is completely shifting toward cloud-based solutions for better management and access [37][38][39][40][41][42][43][44][45], which extends from smart cities to smart home applications [46][47][48][49][50][51][52]. Small startup and companies can easily start their services with the help of Cloud computing solutions at a lower cost [53][54][55][56][57][58][59]. It is easy to manage and access the services and provide services 24/7 [60][61][62][63][64][65][66].…”
Section: Sdn-enabled Cloud Computingmentioning
confidence: 99%